Ativos culturais: um estudo de caso da implementação dos procedimentos contábeis patrimoniais - Oliveira, Tereza Lúcia Ribeiro de (2022)
The valuation of cultural assets is a relevant topic that has required research and market attention. Valuation methods have been proposed and International Accounting Standards have formalized the issue in order to settle divergences. Public Accounting in Brazil has sought to converge with International Accounting Standards that address the issue of implementing Asset Accounting Procedures. This work aims to evaluate the methodologies for valuing cultural assets and to carry out a case study evaluating the stage at which the implementation of the valuation of cultural assets under the tutelage of a public university in Brazil, where there is a regulation on the theme aimed at guiding asset management and providing more transparency and fidelity to the accounting information of public bodies. The recommendations found in regulations applied to the public sector propose the use of fair value to measure assets incorporated into cultural assets. The methodology adopted is a bibliographical and documentary review with a qualitative approach. Analysis of materials and documents was used as a research tool to collect data on the implementation of new legal requirements. A case study was carried out, ending with the analysis and interpretation of the data obtained, comparing the data collected with the guidelines of the legislation. Implementing the economic valuation of these existing collections goes beyond legal compliance, it represents a way to optimize available resources and feed management systems for these equipment with greater efficiency. From the investigated material, information was extracted that reports the proper application of the fair value method as a way of valuing the cultural assets of the institution that has its cultural assets duly inventoried and valued, in the process an inflow of new assets was created that when incorporated into the heritage, they are duly valued through the treatment proposed for their recognition, measurement and disclosure in the public heritage in accordance with the legal framework.